UTILIZATION OF Salvinia molesta AS Fe(II) AND Mn(II) ADSORBENTS - Wiranata, Muhammad Harjan; Sitorus, Saibun; Widodo, Nanang Tri (JURNAL ATOMIK, 2020)
Research on utilization of Kiambang powder (Salvinia molesta) as adsorbent Fe (II) and Mn (II) in artificial samples. The method used is adsorption with a modified activated adsorbent. From the results of the study obtained optimum conditions for adsorption of Fe (II) at pH of 4, time of 30 minutes and adsorption capacity of 0.158 mg/g. The optimum conditions for the adsorption of Mn metal ions at pH of 6, time of 60 minutes and adsorption capacity of 2.522 mg/g.